Implementation of Vygotsky’s Constructivism Learning Theory through Project-Based Learning (PjBL) in Elementary Science Education - Siregar, Trio Erawati; Luali, Nihayatul; Vinalistyosari, Risca Canda; Hanurawan, Fattah; Anggraini, Ade Eka (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
The study aims to describe the implementation of planning, implementation and evaluation of learning of Vygotsky constructivism through project-based learning on IPA exploration. This research uses a qualitative approach to the type of case study research. A case study is an enquiry to investigate phenomena occurring on the ground. This research was conducted at SDN Mojolangu 3 Kota Malang and the research subjects were 3 class teachers, students of 4.5 and 6. Data was collected through interview techniques, observations, and documentation. Data analysis is carried out in three stages: data reduction, data presentation, and conclusion delivery. The initial phase analysis is done by designing learning to determine the theme of the project, determine the implementation, and carry out evaluations to find out the project's success. Research results show that the application of Vygotsky learning through project-based learning to IPa learning can create new experiences for students and attract attention. Vygotsky's approach to constructivism emphasises student-centred learning in the acquisition of knowledge and the process of interaction with the social environment. Active participation of students in learning as the application of constructivist theory can be implemented in project-based learning, where learning project-based learning is one of the learning models that uses projects in problem-solving and student involvement independently through peer mediation in completing a project that has been designed by the teacher.